Some physical properties and relationship between fractions of dabai fruit (Canarium Odontophyllum Miq.) variety ‘Ngemah’ - Shamsudin, R.; Ariffin, S.H.; Zainol @ Abdullah, W.N.Z.; Azmi, N.S.; Halim, A.A.A. (Rynnye Lyan Resources, 2024)
Some physical properties of different fractions part of dabai fruit were determined for useful application in appropriate mathematical models for the process optimization and designing processing equipment. The objective of this study was to determine and compare some physical properties of three different fractions (whole, kernel and nut) by measuring the dabai fruit. Based on the result, the whole fruit reported the highest value in terms of length (L) (39.14 mm), thickness (T) (22.76 mm), geometric mean diameter (Dg) (26.86 mm), arithmetic mean diameter (Da) (27.89mm), surface area (2269.80 mm2), mass (12.38 g), volume (11300 mm3), sphericity (68.67%), and aspect ratio (Ra) (55.69%). On the other hand, the true density, bulk density, and porosity, the nut fraction has the highest values with 2755.0 kg/m3, 738.180 kg/m3 and 71.44%, respectively. Based on principal component analysis (PCA), the first principal component has a large positive association with L, T, W, mass, Ra, Dg, Da and surface area. Meanwhile, there is a large negative association with true density and porosity for the second component analysis.